Critical Success Factors of Project Management in Nepalese Hydropower Projects - Thapa, Raju; Shrestha, Santosh Kumar (Journal of Advanced College of Engineering and Management, 2018)
The delay in the construction industry is a global phenomenon and the construction industry in Nepal can!t be the exception. To deliver the project product on time, within the budget, of quality in the safest manner is the goal of project management. Even potentially good projects are failing because of the weak project management performance in Nepalese construction projects. Due to the lack of research based findings in these areas, the new project managers are facing problems about in which areas they need to focus for successful delivery of the project. The purpose of this research is to find out the critical success factors of project management that help the project parties reach their goal as planned in Nepalese hydropower projects. In this study, general success factors of project management were collected from various literatures and the pilot survey, rank them based on relative importance index (RII), and found top seven success factors as critical success factor. Based on the 85 responses from project managers and experts working in hydropower projects in the first stage study, top seven success factors of project management were Effective communication between project team members (S1), Job satisfaction of project team members (S2), Timely decision by client (S3), Competence of the project manager (S4), Effective coordination between stakeholders, public institutions (S5), Competence of the project team members (S6), Proper and timely supervision (S7).